The Influence of Price Discounts and In-Store Display on Impulse Buying Decisions on Rabbani Pekanbaru Products (Study on Rabbani Pekanbaru Consumers) - Putri, Ririn Aisyah; Mandataris (Formosa Journal of Multidisciplinary Research, 2024)
This study seeks to investigate how price reductions and in-store displays influence impulsive purchasing choices among customers of Pekanbaru Rabbani items. The approach utilized in this study involves descriptive and quantitative statistics within an explanatory research framework. The study included 89 participants selected using Accidental Sampling and data was collected using a questionnaire. The data analysis, which involved validity testing, reliability testing, linear regression analysis, hypothesis testing, and coefficient of determination testing, indicates that price discounts significantly influence impulse buying. In-store displays also have a significant impact on impulse buying. Furthermore, the combined effects of price discounts and in-store displays on impulse buying decisions for Rabbani Pekanbaru products are significant.